2018
DOI: 10.35670/1667-4545.v18.n2.20801
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación y validación de un instrumento para evaluar el constructo compasión

Abstract: <p>El presente estudio tuvo por objetivo la traducción y validación de The Compassion Of Others’ Lives scale (COOL; Escala de Compasión hacia Otros; Chang, Fresco, &amp; Green, 2014), evaluando su funcionamiento en una población de adolescentes y adultos jóvenes argentinos. El estudio empírico instrumental se realizó a partir de un muestreo no probabilístico, con la participación de 385 adolescentes y adultos jóvenes, 210 mujeres y 175 varones de 13 a 23 años (M = 17.32; DE = 2.51). Para estudiar las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
3
0
4
Order By: Relevance
“…Strauss et al ( 2016 ) defined compassion as a cognitive, affective and behavioral process that involves identifying suffering, understanding its universality, feeling emotionally connected or empathic with the experience of the other, tolerating uncomfortable feelings in response to suffering and being motivated to alleviate it/act. This definition is consistent with the description given by studies of the elements that make up compassion (Flores et al, 2018 ; Klos & Lemos, 2018 ; Sacristán-Martin et al, 2019 ; Valentín et al, 2019 ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Strauss et al ( 2016 ) defined compassion as a cognitive, affective and behavioral process that involves identifying suffering, understanding its universality, feeling emotionally connected or empathic with the experience of the other, tolerating uncomfortable feelings in response to suffering and being motivated to alleviate it/act. This definition is consistent with the description given by studies of the elements that make up compassion (Flores et al, 2018 ; Klos & Lemos, 2018 ; Sacristán-Martin et al, 2019 ; Valentín et al, 2019 ).…”
Section: Resultssupporting
confidence: 87%
“…However, it has been identified that all definitions have two elements in common: the recognition of suffering and the active component that motivates it to alleviate it. It should be noted that four studies (Asensio-Martínez et al, 2019 ; Elices et al, 2017 ; Klos & Lemos, 2018 ; Montero-Marin et al, 2016 ) have a common definition, in which they categorize compassion as a complex construct or process involving cognitive, affective and behavioral characteristics in a situation of suffering. This is a multidimensional understanding of compassion that differs from other works that provide one-dimensional conceptualizations, limiting compassion to a feeling, a trait or a virtue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La compasión y la preocupación frente a una experiencia negativa de otros han sido consideradas tanto constructos relacionados al de empatía, particularmente cuando se considera a la empatía desde un punto de vista cognitivo (Marsh, 2011), como componentes de la dimensión emocional de la empatía, incluidos en la evaluación del constructo con medidas, como el IRI (Davis, 1980;Mestre-Escrivá et al, 2004). Con base en esta evidencia, se propone evaluar la validez convergente del TECA, analizando la relación entre sus puntuaciones y las puntuaciones en un test de compasión, The Compassion of Others' Lives Scale (COOL; Chang et al, 2014) en su adaptación a la Argentina (Klos & Lemos, 2018).…”
Section: Tabla 1 Escalas De Empatía Para Adolescentes Y Adultosunclassified
“…Los valores de consistencia interna obtenidos en este segundo estudio fueron: Alegría empática TECA Ω = 0,71, Estrés empático TECA Ω = 0,79, Comprensión emocional TECA Ω = 0,66 y Adopción de perspectiva TECA Ω = 0,68. (Klos & Lemos, 2018). La COOL evalúa el constructo compasión hacia otros y está conformada por 26 ítems, de los cuales 13 corresponden a la dimensión de Empatía (e.g., "Tengo la habilidad de ponerme en el lugar de otros") y 13 a Alivio de Sufrimiento (e.g., "Estoy dispuesto a ayudar a quien lo necesita sin importar si esto me beneficia") presentados en un formato de escala Likert de 7 puntos, que va desde 1 = Fuertemente en desacuerdo, hasta 7 = Fuertemente de acuerdo.…”
Section: Instrumentosunclassified